Sex‐specific peripheral and central responses to stress‐induced depression and treatment in a mouse model. Issue 12 (11th September 2020) - Deonaraine, Kristina K.; Wang, Qian; Cheng, Haoxiang; Chan, Kenny L.; Lin, Hsiao‐Yun; Liu, Kalena; Parise, Lyonna F.; Cathomas, Flurin; Leclair, Katherine B.; Flanigan, Meghan E.; Li, Long; Aleyasin, Hossein; et al.
Abstract: Major depressive disorder affects ~20% of the world population and is characterized by strong sexual dimorphism with females being two to three times more likely to develop this disorder. Previously, we demonstrated that a combination therapy with dihydrocaffeic acid and malvidin‐glucoside to synergistically target peripheral inflammation and stress‐induced synaptic maladaptation in the brain was effective in alleviating chronic social defeat stress (CSDS)‐induced depression‐like phenotype in male mice. Here, we test the combination therapy in a female CSDS model for depression and compared sex‐specific responses to stress in the periphery and the central nervous system. Similar to male mice, the combination treatment is also effective in promoting resilience against the CSDS‐induced depression‐like behavior in female mice. However, there are sex‐specific differences in peripheral immune responses and differential gene regulation in the prefrontal cortex to chronic stress and to the treatment. These data indicate that while therapeutic approaches to combat stress‐related disorders may be effective in both sexes, the mechanisms underlying these effects differ, emphasizing the need for inclusion of both sexes in preclinical studies using animal models. Abstract : Social defeat stress induces sex‐specific inflammatory cytokine/chemokine responses in the periphery and sex‐specific transcriptional regulation in the prefrontal cortex (PFC). Treatment with dihydrocaffeic acid/malvidin‐glucoside modulates periphery inflammation and gene expression in the prefrontal cortex and alleviates depression‐like phenotype. CSDS, chronic social defeat stress; DHCA, dihydrocaffeic acid.